TINJAUAN KRIMINOLOGI TERJADINYA PERDAGANGAN ORANG DENGAN TUJUAN EKSPLOITASI SEKSUAL TERHADAP PEREMPUAN DAN ANAK DI KOTA PONTIANAK - NIM. A1011211240, ARDI SAMUEL MANURUNG (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT Human trafficking is a form of organised crime that operates rationally to gain the maximum profit from illegal activities that are often carried out using violence and threats. The perpetrators have groups that have been arranged by their superiors and each group has its own tasks, namely: the victim recruitment team, the initial shelter team where the victim will be given a comfortable place so that the victims do not feel suspicious, and the final shelter team where the perpetrators hand over the victim to their mafia boss. The crime of trafficking in persons still faces serious obstacles in its prevention, one of which is due to the fact that the factors behind it have not been comprehensively identified. The purpose of this research is to find out information about how the perpetrators carry out the act of trafficking in persons and also to find out about the factors that make this crime still occur. This research was conducted through descriptive analytical method, with direct and indirect data collection techniques to obtain optimal results using criminological theories. The results showed that the causative factor that made the perpetrators commit the criminal act of trafficking in persons was the criminal market factor that still occurs, where the perpetrators benefit from the criminal market which is used as a business field for selling people. Keywords : Criminology, Human Trafficking, exploitation ABSTRAK Perdagangan orang merupakan bentuk kejahatan terorganisir yang beroperasi secara rasional untuk mendapatkan keuntungan sebesar-besarnya dari aktivitas ilegal yang seringkali dilakukan dengan menggunakan kekerasan dan ancaman. Para pelaku memiliki kelompok yang sudah diatur oleh atasan mereka dan disetiap kelompok sudah memiliki tugas masing